(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The furniture industry has a major impact on environmental sustainability because of its heavy consumption of raw material, energy consumption and waste generation. The growing demand for furniture in India has contributed to a trend toward using synthetic materials and mass production methods, which can harm the environment and traditional craftsmanship. In this study, the potential, applications and suitability of traditional Indian materials like bamboo, solid wood, cane, leather and handloom fabrics for the development of sustainable furniture solutions for present day residential and commercial environment has been explored. The research iFurniture Sustainabilitys qualitative and exploratory which uses secondary data gathered from academic literature, industry reports, case studies, and design publications. The furniture properties of five main furniture areas (living room furniture, bedroom furniture, kids room furniture, outdoor furniture and office / study furniture) were analysed to find appropriate material interventions and sustainable design opportunities. A Design Intervention Matrix was created for analysing the applicability of traditional materials in different furniture types. The results show that indigenous materials have a great potential as renewable, durable, culturally valuable, repairable and environment friendly resources. Moreover, combining traditional craft methods and modular construction with materials contributes to the sustainability of the products and the principles of a circular economy. In conclusion, the study suggests that sustainable furniture design in India is possible by incorporating traditional materials, utilizing the traditional craft skills of the region, and embracing environmentally conscious design principles, which would also help to maintain the rich material and craft heritage of India while contributing to ecological sustainability.